Analysis of Risk Factors for Hypertension and Their Relationship with the Level of Public Awareness in Fakfak Regency - Nur Ain; Rusmawan Awa (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Hypertension is a growing public health concern in Fakfak Regency, West Papua. Secondary health profile data from 2016–2018 indicate a sharp increase in prevalence, from 13.9% in 2016 to 42.8% in 2018. Contributing factors are suspected to include unhealthy lifestyles, inadequate access to healthcare services, and genetic predisposition. The lack of comprehensive health education may have also played a role. Objective: To analyze risk factors associated with the incidence of hypertension in Fakfak Regency during 2016–2018. Methods: This study used a qualitative descriptive design with secondary data obtained from the Fakfak Regency Health Profiles (2016–2018). Data were analyzed to identify trends, patterns, and contributing factors. While some improvements in hypertension management outcomes were observed, they remained below national targets. The limited prioritization of hypertension services before the implementation of the 2019 Minister of Health Regulation on the latest SPM indicators, along with delayed reporting from primary health centers, contributed to low service coverage. Results: The findings indicate a consistent rise in hypertension prevalence over the three-year period. Key contributing factors include lifestyle behaviors, limited healthcare accessibility, and genetic influences. Conclusion: The increasing burden of hypertension in Fakfak Regency highlights the urgent need for comprehensive, multisectoral interventions. Strengthening health education, improving access to care, and conducting further research with primary data are essential for effective prevention and control strategies. Keywords: hypertension, risk factors, community awareness, Fakfak Regency, West Papua